(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the main problems facing organizations that exist today is adapting to the conditions of market economy and to protect the position it has reached in the market. Recently, as the main result of the rapid development of science and technology the world economy put the high quality of produced products and offered services to enterprises as the main requirement. Therefore, entrepreneurs prefer the use of International Standards that have been tested successfully by many enterprises in many developed countries around the world. Compliance with these requirements will give the company the advantages of increasing image, profits, reducing production costs and losses, as well as access to the international market. High quality of the product, its competitiveness and very easy access to foreign markets are achieved by implementing the requirements of International standards such as ISO 9001, GOST P ISO 9001, EQS, GMP, HACCP, QS 9000, OHSAS 18001 etc.